1995
DOI: 10.1002/jmri.1880050105
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging assessment of experimental hepatic dysfunction with mn‐DPDP

Abstract: Manganese (II) N,N'-dipyridoxylethylenediamine-N,N'-diacetate 5,5'-bis(phosphate) (DPDP) is a paramagnetic magnetic resonance (MR) contrast agent that enhances the liver and is predominantly excreted through the biliary tree. The authors evaluated its utility in diffuse liver disease by assessing liver and gallbladder enhancement in 24 rabbits. Total (n = 6) or segmental (n = 6) biliary occlusion or galactosamine-induced hepatitis (n = 6) was induced 3 days before imaging. Six rabbits served as normal controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The efficacy results for the delayed (4 and 24 hours post injection) imaging trial (21) and the safety results for both trials (22) are being reported separately. Already reported elsewhere are the efficacy results from nonclinical studies (5, 23–44) and phases I (6, 45–47) and II (8–18, 48–57) and European phase III 25, 56, 58–65 clinical studies.…”
mentioning
confidence: 99%
“…The efficacy results for the delayed (4 and 24 hours post injection) imaging trial (21) and the safety results for both trials (22) are being reported separately. Already reported elsewhere are the efficacy results from nonclinical studies (5, 23–44) and phases I (6, 45–47) and II (8–18, 48–57) and European phase III 25, 56, 58–65 clinical studies.…”
mentioning
confidence: 99%